2017
DOI: 10.2196/jmir.6581
|View full text |Cite
|
Sign up to set email alerts
|

Complaint-Directed Mini-Interventions for Depressive Complaints: A Randomized Controlled Trial of Unguided Web-Based Self-Help Interventions

Abstract: BackgroundPrevention of depression is important due to the substantial burden of disease associated with it. To this end, we developed a novel, brief, and low-threshold Web-based self-help approach for depressive complaints called complaint-directed mini-interventions (CDMIs). These CDMIs focus on highly prevalent complaints that are demonstrably associated with depression and have a substantial economic impact: stress, sleep problems, and worry.ObjectiveThe aim was to evaluate the effectiveness of the Web-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…This economic evaluation was embedded in a randomized controlled trial (see Lokman et al [19]). The study entailed two-arms in which three web-based CMDIs were compared to a nointervention waiting-list control group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This economic evaluation was embedded in a randomized controlled trial (see Lokman et al [19]). The study entailed two-arms in which three web-based CMDIs were compared to a nointervention waiting-list control group.…”
Section: Methodsmentioning
confidence: 99%
“…These participants were referred to contact their GP or an anonymous online platform for people with suicidal thoughts. The required sample size for this study to achieve a power of 80%, was estimated to be 292 ( 2017 [19].…”
Section: Study Population and Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the online 'Complaint Directed Mini-Interventions' (CDMIs), which were found to be (cost-)effective in a self-guided format [17,18], will be implemented in the primary care setting using a blended care format (i.e. combining the e-health intervention with supporting face-to-face sessions that will be provided by the GP nurse).…”
Section: Introductionmentioning
confidence: 99%
“…The online CDMIs are short, low-threshold unguided web-based interventions that target depressive complaints by focussing on highly prevalent complaints that are demonstrably associated with depression and have a substantial economic impact: stress, sleep problems and worry [19]. There are three different CDMIs: 'Sleep better', 'Stress less' and 'Worry less', and each CDMI contains various modules and exercises (see [18] for more information). A feature of the CDMI intervention framework is that patients can choose the complaints that they want to focus on (by choosing the CDMIs that they want to use), and it also allows patients to choose the modules and exercises that they want to do and in what order (pick and mix).…”
Section: Introductionmentioning
confidence: 99%